2020
DOI: 10.1126/sciadv.aba1593
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin safeguards the ground state of mousepluripotency by strengthening the robustness of the transcriptional apparatus

Abstract: Mouse embryonic stem cells cultured with MEK (mitogen-activated protein kinase kinase) and GSK3 (glycogen synthase kinase 3) inhibitors (2i) more closely resemble the inner cell mass of preimplantation blastocysts than those cultured with SL [serum/leukemia inhibitory factor (LIF)]. The transcriptional mechanisms governing this pluripotent ground state are unresolved. Release of promoter-proximal paused RNA polymerase II (Pol2) is a multistep process necessary for pluripotency and cell cycle gene transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…It is well known that mESCs in the two culture conditions, 2iL and SL, are significantly different. 2iL cells are resilient to many interferences that impair pluripotency in SL cells (Habibi & Stunnenberg, 2017; Zhang et al , 2020). To test whether the mTORC1‐eIF4F axis also controls self‐renewal but not pluripotency in mESCs in SL, we first knocked down Rptor and Rictor .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that mESCs in the two culture conditions, 2iL and SL, are significantly different. 2iL cells are resilient to many interferences that impair pluripotency in SL cells (Habibi & Stunnenberg, 2017; Zhang et al , 2020). To test whether the mTORC1‐eIF4F axis also controls self‐renewal but not pluripotency in mESCs in SL, we first knocked down Rptor and Rictor .…”
Section: Resultsmentioning
confidence: 99%
“…In terms of mechanism, GOLT1B assists the transportation of DVL2 to the cell membrane through its interaction with DVL2, thereby inhibiting the activity of GSK3β and β-catenin degradation [ 41 , 42 ]. Nuclear accumulated β-catenin can bind to the LEF/TCF transcription factor family, which then initiate the transcription of downstream target genes and induces EMT [ 43 45 ]. In addition, the RNA-seq analysis showed that GOLT1B was also related to AMPK and mTOR pathways enrichment, which are correlated to cell metabolism and cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…BRD4 also has a key role in maintaining enhancers, by recruiting CDK9 and the mediator complex ( Di Micco et al, 2014 ). Beyond the direct regulation of pluripotent genes, BRD4 has a complex role in mediating the differences between the 2iLIF ground state and serum + LIF-grown naïve cells, as 2iLIF cells can tolerate the loss of Brd4 , while serum + LIF cells cannot ( Zhang et al, 2020b ). The mechanism involves the inhibition of GSK3 in 2iLIF conditions, which leads to stabilization of beta-catenin, and the recruitment of BRD4 and a multimolecular protein complex to pluripotency genes to make 2iLIF-grown mESCs resistant to differentiation ( Zhang et al, 2020b ).…”
Section: Naïve and Primed Cells In Micementioning
confidence: 99%
“…Beyond the direct regulation of pluripotent genes, BRD4 has a complex role in mediating the differences between the 2iLIF ground state and serum + LIF-grown naïve cells, as 2iLIF cells can tolerate the loss of Brd4 , while serum + LIF cells cannot ( Zhang et al, 2020b ). The mechanism involves the inhibition of GSK3 in 2iLIF conditions, which leads to stabilization of beta-catenin, and the recruitment of BRD4 and a multimolecular protein complex to pluripotency genes to make 2iLIF-grown mESCs resistant to differentiation ( Zhang et al, 2020b ). This results in reduced pause-release of RNA polymerase II (polII) and more stable transcription, which helps explain previous observations that 2iLIF-grown cells have more homogenous gene expression than serum + LIF-grown cells ( Kolodziejczyk et al, 2015 ).…”
Section: Naïve and Primed Cells In Micementioning
confidence: 99%